On solving the profit maximization of small cogeneration systems - Ferreira, Ana C. M. (2012)
Cogeneration is a high-efficiency technology that has been adapted to small and micro scale applications. In this work, the development and test of a numerical optimization model is carried out in order to implement an analysis that will lead to the optimal design of a small cogeneration system. The main idea is the integration of technical and economic aspects in the design of decentralized energy production considering the requirements for energy consumption for the building sector. The nonlinear optimization model was solved in MatLab R environment using two local optimization methods: the Box and the SQP method. The optimal solution provided a positive annual worth and disclosed reasonable values for the decision variables of the thermo-economic model. Both methods converged for the same solution, demonstrating the validity of the implemented approach. This study confirmed that the use of numerical optimization models is of utmost importance in the assessment of energy systems sustainability.